Combining ability analysis for yield and its components in bread wheat (Triticum aestivum L. em. Thell.) - Singh, Khajan; Singh, Udai Bhan; Sharma, Satya Narayan (Journal of Cereal Research, 2013)
Combining ability was analyzed using a half diallel of ten parents in bread wheat (Triticum aestivum L. em. Thell.). Combining ability analysis, revealed the importance of both additive as well as non-additive genetic variances for control of various traits. However, the ratio of Ïƒ2gca/ Ïƒ2sca revealed preponderance of non-additive gene actions in almost all the traits. Parents Raj 4063, HD 2851 and WH 789 were the good general combiners, whereas crosses WH 789 x NW 3015, HUW 468 x UP 2614 and HS 448 x Raj 4063 were found to be best specific combiners for grain yield per plant and some of the yield contributing traits. However on the basis of per se performance and significant sca effects for grain yield per plant and some of its important components, hybrids WH 789 x NW 3015; HS 448 x Raj 4063 and K 209 x HD 2851 were considered to be most promising for further exploitation in breeding programmes.